Bibliometric mapping techniques in educational technology research: A systematic literature review - Jing, Yuhui; Wang, Chengliang; Chen, Yu; Wang, Haoming; Yu, Teng; Shadiev, Rustam (Education and information technologies, 2024)
Bibliometric mapping is widely used in educational technology research to visualize research field development (e.g. the current status and trend). However, there has been limited research examining the present state, challenges, and potential applications of bibliometric mapping techniques in the field of educational technology. In an effort to bridge this knowledge gap, this study conducted a systematic review of 71 articles on bibliometric mapping sourced from 24 journals specializing in educational technology. This review serves as a comprehensive analysis (i.e. a meta-review) of existing reviews in the field. The review focused on productivity, research topics, and research norms. The following key findings were obtained in the study: (1) The field has seen rapid development, with notable author groups, core journals, and major publishing countries; (2) Bibliometric mapping is mainly used for quantitative analysis in five research topics, including specific journals, emerging technologies, learning environments, online and distance learning, and subject concepts; (3) Statistics and evaluations of tools including Bibliometrix package of R language and VOSviewer, databases such as WoS and Scopus, as well as the procedural aspects of the research undertaken, were all considered. Additionally, the study investigated suggested benchmarks for these methods – investigating the availability of recognized reporting guidelines like PRISMA or others, as well as the presence of specific criteria for determining what should be included or excluded when utilizing bibliometric mapping techniques. The study proposed standards for the application of bibliometric mapping techniques in research, accompanied by relevant examples. This study not only reveals the specific value and current applications of bibliometric mapping techniques in educational technology research but also provides clarity on the specific methodologies for their implementation and identifies potential areas for further exploration. Finally, this study puts forth a number of recommendations aimed at fostering the reasoned utilization of bibliometric mapping techniques in the field of educational technology.